SOCIO-LEGAL FOUNDATIONS OF RELIGIOUS EDUCATION IN OUR COUNTRY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article focuses on the concept of education in the Republic of Uzbekistan, the concept of religious and secular education, the right and basis of education, opportunities for religious education, the analysis of the legal framework of religious and secular education, as well as activities in the field of religious education.